The Effects of Leverage and Profitability on Firm Value across Quantile Levels - Putri Andari Ferranti; Cut Edwina (Journal of Fundamental Management (JFM), 2026)
This study examines the effext of leverage and profitability on firm value across different quantile levels. Leverage, profitability, and firm value are measured by debt to equity ratio, return on asset, and enterprise value respectively. The method used is quantile regression. The results show that DER has a positive and statistically significant effect on firm value in the lower and middle quantiles, but its influence weakens and becomes insignificant at higher quantiles. This finding suggests that leverage contributes to value creation primarily for Indonesian infrastructure firms with lower valuation levels, consistent with the trade-off theory, whereas high-performing firms may derive less marginal benefit from additional debt.